Analysis of Inequality in Lampung Province (2014–2021): Sectoral and Regional Approaches - Rachmawatie, Dessy; Prasojo, Prio; Mubarrok, Wafiyulloh (Journal of Economics Research and Social Sciences, 2024)
Lampung as one of the provinces in Indonesia that cannot be separated from the problem of inequality in economic and regional development. From the Gini ration data of Lampung Province, both urban and rural, there was a decrease where the gini ration in 2020 was 0.320, then in 2021 it was 0.314, while in 2022 it was 0.313, from the gini ration data in the last 3 years there was a significant decrease. Lampung which consists of 13 districts and 2 cities has problems in development, namely: problems of economic growth, regional inequality, and inequality of income distribution. The aspect of equitable distribution of territory and income is very important to achieve because equitable distribution of development results is one of the strategies and goals of national development in Indonesia. Development inequality between regions, where on the one hand there are regions that are rapidly advancing and developing, but on the other hand there are also areas that are relatively lagging in terms of development. Thus, this study aims to analyze the level of inequality between regions and clustering districts / cities in Lampung Province in 2014-2021. The data used in this study are secondary data with a research period of 2014-2021. The models used are Williamson Index analysis and Klassen Typology analysis. Based on the results of the study, it shows that the level of regional inequality between districts/cities in Lampung Province in 2014-2021 is still relatively low but tends to decrease every year, where the inequality is caused by the positive contribution of South Lampung Regency, Central Lampung Regency, Tulang Bawang Regency, Mesuji Regency, and Bandar Lampung City.